Surgical outcomes for chronic exertional compartment syndrome following improved diagnostic criteria. Issue Volume 166:Issue E(2020) (16th April 2019) - Simpson, Christopher; Roscoe, D; Hughes, S; Hulse, D; Guthrie, H
Abstract : Introduction: Chronic exertional compartment syndrome (CECS) presents with pain during exercise, most commonly within the anterior compartment of the lower limb. A diagnosis is classically made from a typical history and the measurement of intramuscular compartmental pressure (IMCP) testing. Improved, more specific diagnostic criteria for IMCP testing allow clinicians to now be more certain of a diagnosis of CECS. Outcomes following surgical treatment in patients diagnosed using these more robust criteria are unknown. Methods: All patients undergoing fasciectomy for anterior compartment CECS at a single rehabilitation unit were identified between 2014 and 2017. Wilcoxen signed-rank test was used to compare military fitness grading and paired t-test was used to compare Foot and Ankle Ability Measure, FAAM Sport Specific and Exercise-Induced LimbPain-G outcome measures, presurgery and postsurgery. Results: There was a significant difference in fitness grading between presurgical and postsurgical intervention (Z = −2.68, p < 0.01) with 46 % of patients improving their occupational medical grading. All secondary measures of outcome, looking at clinical symptoms, also improved. Conclusion: Almost half of the patients undergoing fasciectomy, following diagnosis using more specific criteria, will have an improvement in occupational medical grading. These outcomes represent the lower end of those reported in civilian populations. This is likely a result of a combination of factors, most notably the different diagnostic criteria followed and the more stringent criteria applied to military occupational grading, compared with civilian practice. Further work is now required to evaluate the impact of differing rehabilitation regimes on postoperative patients identified through this more specific diagnostic testing.